Kewenangan Penetapan dan Pelantikan Raja Negeri Tulehu oleh Kepala Pemerintah Kabupaten Maluku Tengah - Ohorella, Nurjanah; Sedubun, Victor Juzuf; Nendissa, Reny Heronia (Faculty of Law, Universitas Pattimura, 2022)
Introductioan: The regent's authority in the rural scope is the authority to regulate the administration of regional areas that fall within the scope of his government administration, namely the village or sub-district.Purposes of the Research: The purpose of this paper is to find out the Authority of the Appointment and Inauguration of the King of Tulehu by the Head of the Central Maluku Regency Government.Methods of the Research: The research method used is normative juridical, the approach used in this research is the statutory approach, conceptual approach and case approach. Sources of legal materials used are primary legal materials, secondary and tertiary legal materials. The technique of collecting legal materials carried out in this research is through a literature study, then analyzed using qualitative methods.Results of the Research: The Regent is not authorized to stipulate and inaugurate the Head of the Tulehu State Government who is directly and publicly elected and is not in accordance with the customary law applicable in the Tulehu State because the Central Maluku Regent's authority as stated in PERDA Kabupaten Maluku Tengah No 3/2006 is stated to only inaugurate and In the process, it is given to the customary law procession of each customary land to carry out the nomination process as part of the State's recognition of the existence of the customary law of the community which is still valid today. The legal consequences of the presence of the Central Maluku Regent's Decree are: SK for Replacement of State Sanir Number: 147 - 512 of 2019. and SK of Ratification of New State Sanir Number: 141.05 - 522 of 2019.